Does emergency surgery have an impact on lymph node harvest in colorectal cancer surgery? – Single center experience - Nikolovski, Andrej; Dervishov Kristijan; Ulusoy, Cemal (Springer, 2021)
Background: Adequate oncologic surgery for colorectal cancer implies proper resection margin of the resected specimen and complete mesocolic excision in order to achieve objective postoperative pathologic staging. Current recommendations require a minimum of 12 lymph nodes retrieval. In emergency colon cancer surgery, questions are raised about its impact on the lymph node number harvest. Methods: Retrospective analysis of 102 patients operated for colorectal cancer in the period of 1 year was conducted. Two groups (emergency and elective) were formed. Six surgeons performed all of the operations (three high-volume and three low-volume surgeons). Results: Twenty patients presented as surgical emergencies and the rest 66 were elective cases. Sixteen patients with stage IV were excluded. Mean number of lymph nodes retrieved in the emergency group was 11.1 [5–20], and 14.7 [4–34] in the elective one, respectively (p=0.004). Sufcient number of lymph nodes (>=12) extraction was achieved in 7 patients in the emergency group and in 48 patients in the elective one (p=0.003). Conclusions: Emergency colon cancer surgery did have impact on the lymph node number harvest. Adequate colorectal training is expected to improve the surgical technique in order to achieve reliable TNM staging
Keywords: Colorectal cancer; Lymph node